Bile salt–bile salt interaction in mixed monolayer and mixed micelle formation. (January 2019) - Azum, Naved; Rub, Malik Abdul; Asiri, Abdullah M.
Highlights: Interaction between bile salt mixtures has been investigated. The critical micelle concentration and interaction parameter were determined. The synergistic behavior was observed for the NaC + NaDC mixtures while NaC + NaTC show antagonism. Thermodynamic properties of micellization were calculated. Aggregation number (N), Stern-Volmer constant and dielectric constant were computed. Abstract: Surface tension and steady-state fluorescence measurements have been done for mixtures of bile salts, namely sodium cholate (NaC) + sodium tourocholate (NaTC) and sodium cholate + sodium de-oxycholate (NaDC) at 298.15 K. From the experimental critical micelle concentration ( cmc ), the interaction parameter has been figured utilizing the regular solution theory proposed by Rubingh for mixed surfactant systems. The ideal cmc values and thermodynamic properties of micellization were evaluated. The Rosen model was used to calculate the various surface parameters. The interaction between NaC + NaDC surfactants was observed to be stronger than in NaC + NaTC. The stronger interaction of NaC + NaDC was also confirmed by fluorescence data. The steady-state fluorescence quenching method was applied to compute the micelle aggregation number, Stern-Volmer constant and micropolarity of single and mixed bile salt systems.